Factors Relationship with Fly Density Level in Telanaipura Subdistrict Temporary Waste Storage - Arnild Augina Mekarisce; Maijon Jumpatua Purba; Samsidar Samsidar; Zuli Rodhiyah; Fitria Eka Putri; Fajrina Hidayati; Ashar Nuzulul Putra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Fly density is an indicator of environmental sanitation assessment. Fly density is influenced by waste management, the National Waste Management Information System (SIPSN) shows that waste generation in Jambi City reaches 159,688.01 tons/year. The aim of this research is to determine factors related to the level of fly density in Temporary Waste Storage Sites (TPSS) in Telanaipura District, Jambi City 2023. This research is a quantitative research with a cross sectional method research design. This research was conducted in the Telanaipura District community with a sample of 94 people. Data analysis was carried out using univariate and bivariate methods using correlation tests. The results of this study indicate that knowledge (p=0.027), action (p=0.029), monitoring (p=0.017), sorting (p=0.016), collection (p=0.027), and transportation (p=0.026) have relationship with the level of fly density, while attitude (p=0.245) had no relationship with the level of fly density. Knowledge, action, monitoring, sorting, collection and transportation are factors related to the level of fly density in temporary waste storage sites in Telanaipura District. It is hoped that the public will pay attention to managing household waste properly.